Top 50 military aircraft - Newdick, Thomas (Amber Books, 2017)
From the Fokker biplanes to World War II fighters like the Supermarine Spitfire and Messerschmitt Bf 109, and from heft bombers like the Boeing B-17 to Cold War classics such as the MiG-21 and on to stealth aircraft such as the SR-71 and Lockheed Martin F-22 Raptor, each entry in 'Top 50 Military Aircraft' tells you all you need to know about the best there has been. From propeller aircraft to jets, from fighters to bombers to transport aircraft, the most impressive aircraft from more than a century of military aviation have been selected.